A bandwidth‐agile balanced filtering power divider. Issue 7 (23rd March 2019) - Tan, Zhen; Lu, Qing‐Yuan; Yu, Wei; Chen, Jian‐Xin
Abstract: In this article, a balanced filtering power divider (FPD) that allows for operational agility of the bandwidth (BW) is presented. The differential‐mode power dividing and high common‐mode (CM) suppression can be realized by microstrip‐to‐slotline transition. Two slotline open stubs with different lengths are added in shunt to the main slotline for the transition, which can not only introduce transmission poles for extending and controlling transition BW, but also generate two extra transmission zeros (TZs) near to the passband edges, featuring good filtering response. The two transmission poles can be independently tunable by loading varactors to the open ends of slotline stubs and two TZs will be changed accordingly so that the filtering passband BW is electrically tunable. To verify the theoretical prediction, a prototype of tunable balanced FPD is fabricated and measured. The measured results show that the 3‐dB fractional bandwidth (FBW) of the passband varies from 5.6% to 12.6%, meaning more than a double tuning range for the FBW, and the CM suppression is better than 40 dB across the frequency band of interest.